AFTER COVID-19 QUALITY OF LIFE - Khusainova Munira Alisherovna; Kamolova Diyora Djamshedovna (Journals Park Publishing, 2024)
Objective: to assess the quality of life of patients who have suffered from COVID-19 with a severe course of the disease, as a result of comprehensive rehabilitation measures. Materials and methods. The article presents the results of studying the quality of life of 30 patients (13 men and 17 women) who underwent COVID-19 with severe course after inpatient treatment. The average age was 49.8±1.42 years. 28 age-matched patients who were not ill with COVID-19 were taken as a control group. The studies were conducted in the polyclinic day hospital The assessment of the quality of life (QOL) of patients was carried out using the SF-36 questionnaire (The Short Form-36) before and after rehabilitation measures. The questionnaire consists of 36 items on 8 scales. At the same time, numerical indicators of the sum of points close to 100 indicated a high quality of life, and closer to 0 – low. Results and discussions. When analyzing the results of QOL in patients with COVID-19 on the SF-36 scale compared with the control group in patients with severe disease, we found a significant decrease in the overall indicator by 29.9%. At the same time, the average score for the physical component It was 35.4±4.0.3 points, role functioning (RP) -39.5±5.5, psychological status - 55.2±1.94. Decrease in indicators by 45%, 33.5% and 20.2%, respectively (p<0.05). 2 weeks after the rehabilitation measures, when assessing the QL data, there was a significant improvement in all parameters (p<0.05), except for the aspect of "Role functioning (RP)" (p≥0.05), which indicated a significant restriction of physical activity due to the physical condition of the patient. Conclusion. The study of QOL in patients who underwent COVID-19 in severe form indicated that a significant decrease in all indicators. At the same time, these shifts were especially related to the physical component, mainly due to physical functioning (PF) and role functioning (RP). Evaluation of the results of the implementation of an individual rehabilitation plan aimed at lung recovery after COVID-19 showed an improvement in clinical condition and QOL, mainly due to indicators of physical functioning. At the same time, the changes in the aspect of role functioning turned out to be insignificant.
Keywords: COVID-19, quality of life.